Steps to Improved Firm Performance with Business Process Management: Adding Business Value with Business Process Management and its Systems - Hyötyläinen, Tahvo (Springer, 2015)
​Business Process Management (BPM) has become a widely adopted management approach, prompting significant investments by private and public companies since 2000. Since neither the concept of BPM nor the factors leading to successful BPM initiatives are grounded in theory and also lack empirical support, Tahvo Hyötyläinen explores what business value BPM and BPM Systems can cause and how they can bring about improved firm performance. The author’s main implication is to show how to enhance the probability of success with BPM and its Systems. His research also adds to the understanding on how to increase customer-centricity –an empirically supported yet less studied direction of BPM.